Corpo em devir: entre a floresta e a cidade - Albuquerque, Mariana Pelizer de (2017)
This thesis emerge out of a deep uneasiness produced by the experience of moving to live and settling in the city of Manaus, which forced me to think in order to combat the paralysis that took over my body. Writing follows the flow of a poetic, critical and potent body that transmutes itself into a terrified body, frozen in apathy, in the pain of the end of the world, in the pain of a people; a process presented through cartographic method investigation, in which accuracy refers to the capability of the latter to say the unspeakable so that it becomes sensory. The work is developed with the purpose of elucidating manauara's subjectivity, resulting from the traumas of the high degree of violence of the colonial-capitalist regime in the region, but also from the resistance of the forest's force, the intense tropical climate and the indigenous ancestral knowledge that insists on staying alive. The text unfolds in a quest for ways to displace myself from paralysis and to re-appropriate the seized vital drive. Performance-art then emerges as a clinical and performative device that transmutes a paralyzed body into a living body, dilating affections, creating new machineries, potentiating encounters with the city